2020
DOI: 10.17784/mtprehabjournal.2020.18.791
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effect of proprioceptive neuromuscular facilitation on scapular dyskinesia of volleyball players

Abstract: Background: Scapular dyskinesia can be caused by several factors, such as poor posture (thoracic kyphosis or cervical hyperlordosis) or changes in the activation and coordination of the scapular stabilizing muscles. Therefore, the term is correctly used when there is a change in the scapular biomechanics at rest or during movement. Objective: The objective of this study was to evaluate the effects of PNF on scapular dyskinesia of volleyball players. Methods: This is a quasi-experimental study with volleyball p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We believe that these PNF patterns would optimize the strength imbalance between UT with both LT and SA in individuals with scapular dyskinesis. Several studies showed the effectiveness of PNF training in different shoulder problems (20,37,38). In a case study, it was concluded that scapular patterns of PNF application was an alternative and effective option when standard strengthening, mobilization or electrotherapy modalities were not efficient in patient with subacromial impingement syndrome and scapular dyskinesis (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that these PNF patterns would optimize the strength imbalance between UT with both LT and SA in individuals with scapular dyskinesis. Several studies showed the effectiveness of PNF training in different shoulder problems (20,37,38). In a case study, it was concluded that scapular patterns of PNF application was an alternative and effective option when standard strengthening, mobilization or electrotherapy modalities were not efficient in patient with subacromial impingement syndrome and scapular dyskinesis (37).…”
Section: Discussionmentioning
confidence: 99%
“…In a case study, it was concluded that scapular patterns of PNF application was an alternative and effective option when standard strengthening, mobilization or electrotherapy modalities were not efficient in patient with subacromial impingement syndrome and scapular dyskinesis (37). Meneghini et al (38), examined the immediate effect of scapula PNF patterns in 32 volleyball players with scapular dyskinesis; the authors showed that the number of individuals with scapular dyskinesis decreased after the scapular PNF training. Balcı et al (20) stated that a combination of scapular PNF patterns with physiotherapy modalities was effective in improving shoulder function and ROM, while reducing pain in patients with adhesive capsulitis.…”
Section: Discussionmentioning
confidence: 99%